PENDEKATAN HUKUM PIDANA TERHADAP KEPEMILIKAN TANAH ABSENTEE SEBAGAI BENTUK PERLINDUNGAN HUKUM OLEH NEGARA - Nainggolan, Samuel Dharma Putra; Negara, Dharma Setiawan (Veteran Law Review, 2023)
The enactment of the Basic Agrarian Law (UUPA) has changed the constellation of land in Indonesia. The spirit of anti-colonialism is eliminated as much as possible in the regulation of land in Indonesia. There is land that functions as agricultural land that is owned by parties who do not even live where the land is located, known as Absentee. This can hurt the spirit of the UUPA which wants to protect land ownership by indigenous people who live where the land is located. It is felt that the criminal law approach needs to be considered in an effort to protect the spirit of the BAL, in this case absentee land ownership. This legal research is normative legal research using a statutory approach, a conceptual approach that aims to analyze the criminal law approach to absentee land ownership in realizing social justice for all Indonesian people.